Comparative Analysis of Ethical and Legal Principles in the Islamic Business Management Model - Agustian, Kresnawidiansyah; Hejazziey, Djawahir; Zen, Agustian; Sekarini, Ratih Ayu; Wiwin, Wiwin (ADMAN: Journal of Contemporary Administration and Management, 2023)
In recent decades, businesses based on Islamic principles have experienced significant growth. Business models that are in line with Islamic values have become a major concern for Islamic business and economic actors. This phenomenon has triggered intense discussions on the impact of ethics and Islamic law on Islamic business practices. This study will analyse the comparison between ethics and Islamic law in the context of Islamic business. This research is a qualitative literature study that incorporates data from 1991 to 2023 taken from sources found on Google Scholar. The qualitative literature review research method is used to investigate, analyse, and compile a comprehensive understanding of developments, trends, and significant findings in various fields of knowledge relevant to the topic of this research. The results show that business management in the Islamic context is based on ethical and legal principles derived from Islamic religious teachings. These principles complement each other and form the basis for the Islamic business management model. Ethical principles, such as taqwa, good deeds, justice and ihsan, encourage integrity, honesty and social responsibility in business. Meanwhile, legal principles, involving sharia, contracts, zakat, waqf, haram, and halal, govern the legal aspects of business, ensuring compliance with Islamic values and rules.